Features of Renewables in Energy Projection of Turkey in view of Energy Supply and Demand Scenarios - Ozcira, S.; Aycicek, E.; Onel, I. Y. (IEEE, 2009)
In this study, energy demand structure and the latest growth trends, energy production using different resources, distribution and integration structures, investment, support and taxing structures and characteristics of electricity industry of Turkey are presented, integration of renewables in electricity markets are explicated and the reasons of a probable near future energy shortage are analyzed. Main priorities expected to be targeted during every energy sector related reform in Turkey are determined.
Keywords: Electricity marketing; energy projection; feasibility; renewable energy; Engineering